Smac127 Has Proapoptotic and Anti-Inflammatory Effects on Rheumatoid Arthritis Fibroblast-Like Synoviocytes - D. Lattuada; R. Gualtierotti; K. Crotta; P. Seneci; F. Ingegnoli; C. Corradini; R. Viganò; O. Marelli; C. Casnici (Hindawi Limited, 2016)
Rheumatoid arthritis (RA) is characterized by synovial inflammation and hyperplasia. Fibroblast-like synoviocytes (FLSs) are apoptosis-resistant and contribute to the pathogenesis of RA by producing cytokines and proteolytic enzymes, which degrade the extracellular matrix. We evaluated the proapoptotic and anti-inflammatory activity of the small molecule Smac127 on RA-FLSs cultured in synovial fluid (SF), in order to reproduce the physiopathological environmental characteristic of RA joints. In this context, Smac127 induces apoptosis by inhibiting apoptosis proteins (IAPs). This inhibition activates caspase 3 and restores the apoptotic pathway. In addition, Smac127 induces a significant inhibition of the secretion of IL-15 and IL-6, stimulation of pannus formation, and damage of bone and cartilage in RA. Also the secretion of the anti-inflammatory cytokine IL-10 is dramatically increased in the presence of Smac127. The cartilage destruction in RA patients is partly mediated by metalloproteinases; here we show that the MMP-1 production by fibroblasts cultured in SF is significantly antagonized by Smac127. Conversely, this molecule has no significant effects on RANKL and OPG production. Our observations demonstrate that Smac127 has beneficial regulatory effects on inflammatory state of RA-FLSs and suggest a potential use of Smac127 for the control of inflammation and disease progression in RA.